Stream Dissolved Organic Matter Composition Reflects the Riparian Zone, Not Upslope Soils in Boreal Forest Headwaters. Issue 6 (8th June 2018) - Ledesma, J. L. J.; Kothawala, D. N.; Bastviken, P.; Maehder, S.; Grabs, T.; Futter, M. N.
Abstract: Despite the strong quantitative evidence that riparian zones (RZs) are the dominant source of dissolved organic carbon (DOC) to boreal streams, there is still a debate about the potential contribution of upslope areas to fluvial carbon export. To shed new light into this debate, we investigated the molecular composition of dissolved organic matter (DOM) in four upslope‐riparian‐stream transects in a Northern Swedish forest catchment using absorbance (A254 /A365 and SUVA254 ) and fluorescence (fluorescence and freshness indices) metrics. Based on these metrics, our results indicate that stream water DOM molecular composition resembles that of RZs and significantly differs from that of upslope areas. The resemblance between stream and riparian DOM was most apparent for the "Dominant Source Layer" (DSL), a narrow RZ stratum that, theoretically, contributes the most to solute and water fluxes to streams. Spectroscopic characterization based on traditional interpretations of the metrics suggested that mineral upslope (podzol) DOM is less aromatic, more microbially derived, and more recently produced than organic riparian (histosol) and stream DOM. We conclude that RZs, and specifically DSLs, are the main sources of DOC to boreal headwater streams and potentially to other streams located in low‐gradient, organic matter‐rich catchments. Plain Language Summary: Understanding carbon cycling in natural ecosystems is critical because ongoing climate change can promote the release of previously stored carbon in forest soils to streams and rivers, with the potential to form carbon dioxide, the main greenhouse gas. This is particularly important in boreal ecosystems, which are the largest stores of terrestrial carbon in the world. In this study, we identify the near‐stream area, the so‐called riparian zone, as the main source of carbon from boreal forest soils to streams. We provide qualitative data to support this, which together with previous quantitative analyses, make up enough evidence to support that the riparian zone is the main source of carbon to streams. As there is still a debate about the potential contribution of other areas in the ecosystem to the fluvial carbon export, our study importantly highlights that the riparian zone should be the focus of scientific assessments and management strategies in relation to carbon exports in surface waters. Key Points: Stream water DOM molecular composition resembles that of riparian zones and differs from that of upslope areas in boreal hillslope transects The resemblance between stream and riparian DOM is most apparent for the riparian "Dominant Source Layer" Mineral upslope (podzol) DOM is less aromatic, more microbially derived, and more recently produced than organic riparian (histosol) DOM